Predicting Brand Loyalty to Manufacturer-Sponsored Brands in an Omnichannel Environment : A Configurational Perspective - Sharma, Dinesh; Panda, Tapan Kumar; Sahadev, Sunil (Indian Journal of Marketing, 2025)
Purpose : Drawing upon the configuration perspective, this study examined how combinations of different omnichannel capability dimensions from the supply side lead to brand loyalty for manufacturer-sponsored brands. Omnichannel integration is a long-drawn process that integrates a variety of dimensions. This induced us to understand how various combinations of dimensions lead to loyalty. Design : The study used a multi-level design based on the data collected on 43 manufacturer-sponsor brands from experts and 2,320 consumers through a structured questionnaire. Using the Fuzzy-set qualitative comparative analysis (fsQCA) method, the study explored the different pathways through which seven omnichannel dimensions, namely siloed retail mix, integrated marketing communication, integrated consumer order fulfillment, and information access, continuity of foundationals, rear-end system consolidation, and organization transfiguration, lead to demand-side brand loyalty. Findings : The results showed that these seven omnichannel dimensions are sufficient conditions for achieving brand loyalty. The truth table analysis showed seven pathways for omnichannel integration efforts to improve brand loyalty. Practical Implications : The study presented seven combinations of internal resource-based omnichannel capability dimensions for practical application, which may be implemented to attain loyalty objectives. Originality : This is among the first studies to consider a comprehensive combination of omnichannel integration dimensions and their effects on brand loyalty, unlike previous studies that focused on such limited dimensions. This is also the first study to consider omnichannel integration of manufacturer brands, while previous studies have focused on multi-brand retailers. Further, through a configurational perspective, the study allays the methodological limitations of the variance-based approaches in the previous studies.